Medida teórico-experimental da condutividade de meios porosos usando o método de Boltzmann - Camargo, Mário Augusto (2010)
The hydraulic conductivity is a soil parameter very important to environmental purposes including solute transport and water balance studies. For simulation and planning such parameter has been related to soil physical attributes as easily available as density and texture. With the aim of evaluating experimental and computational conductivities (K) of porous media with a certain complexity it was designed a method based on the use of glycerin as percolate fluid. The glycerin was used due to the restrictions in the Darcy law representativeness for the experiments carried out. It was also utilized the Boltzmann method to simulateK. In order to test the viability of the theoretical methodology two media with analytical solutions for K were used. The results obtained via computational and experimental methods presented a good agreement. After the verification of the validity of the theoretical method for simple geometries, such a method was applied to two new experimental designs with a great level of complexity. In these new cases very good results were obtained between methods (computational and experimental) of K measurement. It was also assessed by the results obtained the limits that should be overcome through the use of more modern computers.